multiplicity of meaning An applied study in the intermediate dictionary - سلمان وداد; الراهب سميرة; شباني بانا (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
This study deals with the issue of the homogeneous lexicon in the intermediate lexicon, and seeks to develop a theoretical approach, and an applied procedure. In the theoretical field, the study is active in defining the Western homonym concept, finding an appropriate Arabic equivalent for it, and distinguishing it from the other term that is stable in Arabic linguistic studies, which is the verbal common. The study also works on finding differences between the two terms: verbal homogeneous and verbal common, and setting standards and rules that distinguish between them. The applied approach focuses on building the lexical text in the intermediate lexicon in particular; Its goal is to describe the reality of the Arabic linguistic lexicon; In order to develop it, and solve its problems, especially with regard to distinguishing between semantics that have common functions, but they may not be of a single etymological origin, and therefore are of the verbal homogeneity that must be distinguished by two independent entries. Finally, it reaches results that may help lexicographers in the future to plan to build an Arabic lexicon that adheres to the latest international lexical standards.